Plantlet regeneration via somatic embryogenesis from mature seed of Citrus nobilis variety SoE from SoE NTT - Agus Purwito, Ali Husni, Kikin H. Mutaqin, Slamet Susanto, Indriati Husain, Fitria Nanda Utami, (Horticultural Biotechnology Research, 2015)
The aim of this research is a study about direct somatic embryogenesis from mature seed and plantlet regenerationÂ of Citrus nobilis variety SoE. Plant material for somatic embryogenesis is the mature seed of Tangerine SoE.Â 6-benzylaminopurine (BAP) 3 mg/L supplemented to Murashige and Skoog (MS) modified medium was inducedÂ direct somatic embryos (SE) 4 weeks after treatments. MS modified medium with single BAP 3 mg/L has resultedÂ the average of eight SE. Nevertheless, average number of SE which resulted from combination BAP 3 mg/LÂ with some level of concentration 2.4-D (0.1, 0.3, and 0.5 mg/L) decreases with increasing the concentration ofÂ 2.4-D. Abscisic acid (ABA) is added at concentration 0.5-3.5 mg/L cannot increase the number of SE, globularÂ early-stage, at 4 and 8 weeks. Gibberellic acid (GA3) added at concentration 2.5 mg/L can increase the growthÂ in the number of normal plantlets this citrus at 8 weeks. Media of enlargement of Tangerine SoE plantlets usedÂ half-strength MS modified medium concentration. This medium can increase the average in height of plantletsÂ at 4 weeks and the average in a number of leaves at 8 weeks. The regenerated plants were acclimatized under the 60% sunlight block and to keep the humidity remains high the plants were lid with UV plastic. The resultsÂ indicated that the plant regeneration via somatic embryogenesis from mature seed of C. nobilis an efficient andÂ effective technique for producing more SE and plant production in large scale. The next sub-cultured in mediumÂ containing GA3 and then the half-strength concentration of medium can increase the number of normal andÂ enlargement plantlets, respectively.Â